Oral parafunctional behaviors, TMD pain, and headaches among patients underwent orthodontic therapy—an observational study - Gałczyńska-Rusin, Małgorzata; Szyszka-Sommerfeld, Liliana; Idzior-Haufa, Małgorzata; Pobudek-Radzikowska, Małgorzata; Woźniak, Krzysztof; Czajka-Jakubowska, Agata (Frontiers in Neurology, 2025)
IntroductionFew studies have evaluated oral behaviors in patients undergoing orthodontic treatment. While occlusal and non-occlusal parafunctions may significantly contribute to TMD symptoms, their frequency in orthodontic patients remains unclear. This study aimed to assess the occurrence of oral parafunctions, TMD pain, and headaches in this population.Materials and methodsThe study included patients undergoing orthodontic treatment with fixed appliances. The Fonseca Anamnestic Index, DC/TMD Axis I, and Oral Behavior Checklist (OBC) questionnaires were used to assess the occurrence of TMD pain and oral parafunctions.ResultsThe study included 152 patients. 59.2% of the study participants were women, the mean age was 20.01 (SD 6.89). The painful form of TMD was found in 23.7% of the study participants, with headaches in 26.4% (with TMD-attributed headaches in 13.2%). The mean score on the OBC questionnaire was 18.96 (SD 8.89) and 25% of patients had high-risk grade of oral behaviors.ConclusionPatients experiencing myalgia, arthralgia, and headaches had notably higher OBC scores. Patients undergoing orthodontic treatment should be screened for oral parafunctions and TMD pain.